KEY DRIVERS OF CORPORATE TAX AVOIDANCE: The Role of Sales Growth, Transfer Pricin, and Business Strategy - Fahira Vanesa Pertiwi; Masripah Masripah (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This research aims to determine the positive influence of sales growth, transfer pricing, and business strategy on tax avoidance of listed manufacturing companies in Indonesia Stock Exchange in the period 2018-2020. The sampling technique used in this study, namely the purposive sampling method with the acquisition of a sampling of 129 samples. The type of this research is quantitative research that uses secondary data based on annual reports and financial reports. Techniques analyzing data in this research used panel data regression model selection test, classical assumption test, hypothesis testing and multiple linear regression. Based on the results of data analysis, it can be concluded that sales growth, transfer pricing, Business strategy, and leverage do not have significant effect on tax avoidance. Meanwhile, profitability has a positive significant effect on tax avoidance. Keywords: Tax Avoidance; Sales Growth; Transfer Pricing; Business Strategy Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh positif pertumbuhan penjualan, transfer pricing, dan strategi bisnis terhadap penghindaran pajak pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2018-2020. Teknik pengambilan sampel yang digunakan dalam penelitian ini yaitu metode purposive sampling dengan perolehan sampel sebanyak 129 sampel. Jenis penelitian ini adalah penelitian kuantitatif yang menggunakan data sekunder berdasarkan laporan tahunan dan laporan keuangan. Teknik analisis data dalam penelitian ini menggunakan uji pemilihan model regresi data panel, uji asumsi klasik, uji hipotesis dan regresi linier berganda. Berdasarkan hasil analisis data dapat disimpulkan bahwa pertumbuhan penjualan, transfer pricing, strategi bisnis, dan leverage tidak berpengaruh signifikan terhadap penghindaran pajak. Sedangkan profitabilitas berpengaruh positif signifikan terhadap penghindaran pajak. Kata Kunci: Penghindaran Pajak; Pertumbuhan Penjualan; Transfer Pricing; Strategi Bisnis